COVID-19-related disruptions to routine vaccination services in India: a survey of paediatric providers - Rajeev Seth; Anita Shet; Preetika Banerjee; Carl Britto; Piyush Gupta (BMJ Publishing Group, 2021)
The COVID-19 pandemic has led to disruptions in essential health services globally. We surveyed Indian paediatric providers on their perceptions of the impact of the pandemic on routine vaccination. Among 424 (survey 1) and 141 (survey 2) respondents representing 26 of 36 Indian states and union territories, complete suspension of vaccination services was reported by 33.4% and 7.8%, respectively. In April-June 2020, 83.1% perceived that vaccination services dropped by half, followed by 32.6% in September 2020, indicating slow resumption of services. Concerns that vaccine coverage gaps can lead to mortality were expressed by 76.6%. Concerted multipronged efforts are needed to sustain gains in vaccination coverage.